ANALISIS SPASIAL SEBARAN LAHAN KRITIS DI KPHP UNIT XII BATANGHARI PROVINSI JAMBI - Eva Achmad; Agus Kurniawan MAstur; Yunita Lestari (Jurnal Belantara, 2021)
Critical land occured as a result of land cover changes from vegetated into non vegetated land or the composition of the vegetation has changed. This study aimed to analyze the distribution of land critical at KPHP Unit XII Batanghari. Critical land analysis was based on the Perdirjen PDASHL Number P.3/PDASHL/SET/KUM.1/7/2018. Land is classified into 5 levels of criticality, namely: non-critical, critical potential, somewhat critical, critical and very critical. The parameters used in determining the level of criticality of the land are: land cover, erosion-prone class, slope class and the presence of land inside or outside the forest function. Spatial analysis used by Geographic Information System (GIS) and remote sensing technology. GIS is able to analyze and represent geographic phenomenon. Landsat 8 imagery was analyzed to obtain land cover clasification. The results of the analysis showed that critical land level of KPHP Unit XI Batanghari consisted of 3,609 ha (4.45%) that classified as very critical and 3,599 ha (4,43%) as critical land. Then, land with a somewhat critical level had the largest area, namely 26,024 ha or 32.07% of the total area of KPHP Unit XII Batanghari. The landcover was the main parameter to determine the level of criticality of the land. The openland cover type had the maximum score 60.